2010
DOI: 10.1038/nrmicro2262
|View full text |Cite
|
Sign up to set email alerts
|

A complex journey: transmission of microbial symbionts

Abstract: The perpetuation of symbioses through host generations relies on symbiont transmission. Horizontally transmitted symbionts are taken up from the environment anew by each host generation, and vertically transmitted symbionts are most often transferred through the female germ line. Mixed modes also exist. In this Review we describe the journey of symbionts from the initial contact to their final residence. We provide an overview of the molecular mechanisms that mediate symbiont attraction and accumulation, inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
691
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 715 publications
(752 citation statements)
references
References 141 publications
12
691
0
2
Order By: Relevance
“…Furthermore, phylogenetic studies of a number of rhizoxinpositive isolates from all the five continents, delivered evidence for host switching of symbionts between fungal lineages (Lackner et al, 2009a), indicating that horizontal transmission has taken place during evolution of the symbiosis, and might still have a role in the natural environment. Yet, in each reproduction cycle of the fungus, B. rhizoxinica is passed on vertically to the next generation, which is a hallmark of close mutualistic relationships (Moran, 2006;Bright and Bulgheresi, 2010). Quite unexpectedly, we observed that the host is not capable of vegetative reproduction in the absence of endosymbionts.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Furthermore, phylogenetic studies of a number of rhizoxinpositive isolates from all the five continents, delivered evidence for host switching of symbionts between fungal lineages (Lackner et al, 2009a), indicating that horizontal transmission has taken place during evolution of the symbiosis, and might still have a role in the natural environment. Yet, in each reproduction cycle of the fungus, B. rhizoxinica is passed on vertically to the next generation, which is a hallmark of close mutualistic relationships (Moran, 2006;Bright and Bulgheresi, 2010). Quite unexpectedly, we observed that the host is not capable of vegetative reproduction in the absence of endosymbionts.…”
Section: Introductionmentioning
confidence: 68%
“…In particular, the transmission of the endosymbionts during host reproduction is a critical step for their survival. Impressive studies document the manifold strategies to ensure a permanent association of bacteria with partners of the animal and plant kingdoms (Dale and Moran, 2006;Moran, 2006;Bright and Bulgheresi, 2010). In stark contrast, nothing is known about the molecular basis of the transmission of endofungal bacteria, that is, bacteria that reside within the fungal cytosol (Kobayashi and Crouch, 2009;Tarkka et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest are host-associated bacteria, including pathogens and symbionts. These diverse bacterial lineages colonize host surfaces, inhabit specific tissues or cells, and can often persist free in soils and or aquatic habitats between phases of host infection [1,2]. The capacity of bacteria to thrive in host tissues is often modulated by the presence of plasmids and genomic islands, cassettes of accessory loci that can get transmitted among genomes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is commonly said that, on the long run, evolution will favour the internalization of symbiotic microbes into the host and their vertical transmission, but what we observe in practice is different: in many cases, such as the ancient and stable legume-rhizobia association, we observe complex intimate interactions, reoccurring in an horizontal way at each generation (Bright and Bulgheresi 2010) (Kiers et al 2003;Oldroyd 2013), instead of vertical transmission.…”
Section: Evolutionary Individuality and Physiological Individuality Dmentioning
confidence: 87%
“…In some cases, for instance in arthropods, many members of the microbiota are transmitted vertically (from parents to offspring). In other cases, for instance in mammals and in many plants, a majority of the members of the microbiota are transmitted horizontally (i.e., they are acquired from the environment) (Bright and Bulgheresi 2010) 19 . In the case of vertical transmission, physiological individuals understood as host-microbe associations can be highly-realised Darwinian individuals, because lineages of these associations can be established.…”
Section: Evolutionary Individuality and Physiological Individuality Dmentioning
confidence: 99%